The Komposisi Jenis dan Struktur Vegetasi Hutan Lindung Bengkunat di Resort III KPH Unit I Pesisir Barat - Sesilia Maharani Putri; Indriyanto Indriyanto; Melya Riniarti (Fakultas Kehutanan Universitas Jambi, 2019)
Bengkunat Protected Forest was the area between the Bukit Barisan Selatan National Park and society settlements. Species composition and vegetation structure were the two things that influenced the complexity’s of forest vegetation. The aims of this research were to identify the species of plants and analyze forest vegetation structure. This research was conducted in March–April 2019 at the 4,470 ha area with the sampling intensity 0.02%. Data collected by the grid line method that was consisting 34 sample plots within the distance 100 m between the plots and 200 m between the lines. The numbers of identified plants species at the research location were 92 species, classified by 34 families and 71 genus. The forest vegetation was consisting by the different growth phases. The seedling phase was the highest density of 4,058.8 species/ha, while the tree phase was lowest density of 262.5 species/ha. The highest canopy cover was the pole phase of 12,186.0 m2/ha (121,9%) and the lowest canopy cover was the seedling phase of 1,838.4 m2/ha (18,4%). The forest crown stratification were consisting of A, B, C, D and E stratum. The highest number of plants were from C strata for 436 trees and the least from A strata of 23 trees with the highest tree is 42 m. Could be concluded that the composition of Bengkunat Protected Forest have so many number of species and complex structure vegetation forest. Key words : Bengkunat Protection Forest , species composition,and vegetation structure.